OBESITAS TERHADAP TINGKAT INSIDENSI HIPERKOLESTEROLEMIA PADA KARYAWAN DPRD PROVINSI SULAWESI SELATAN DESEMBER 2014 - Juliani Ibrahim; Andi Ridha Annisa Rahmat; A.Tenri Padad (Journal Medical Universitas muhammadiyah Makassar, 2018)
To determine the relationship of obesity to incidence rate of hypercholesterolemia on the employees of DPRD Office of South Sulawesi Province. Methods: Analytic observational study with cross sectional design. Samples were employees of the DPRD Office of South Sulawesi Province December 2014. The data were obtained from the primary data through direct examination to determine body mass index and blood cholesterol levels and through a questionnaire and analyzed using SPSS (Statistical Product and Service Solutions) for windows version 21 with Pearson Chi Square test. Results: The number of samples involved in this study were 100 respondents. Most of the samples were classified as obese as many as 81 people (81.0%) and as many as 5 people (5.0%) were classified as non-obese. In as many as 83 people found respondents (83.0%) were hypercholesterolemia and normal only 17 people (17.0%). Conclusion: In this study, the results of a statistical test with a p-value of 0.000. This means that there is a relationship of obesity to incidence rate of hypercholesterolemia on the employees of the DPRD office of South Sulawesi Province December 2014.